Vermicomposting of palm oil empty fruit bunch (EFB) based fertilizer with various organics additives - Lew, J.H. (Institute of Physics Publishing, 2020)
This work aimed at increasing the nutritional content of EFB vermicompost using organic additives at specific initial C:N ratio. Seven batches of composts namely EFB+POME (A) in 1:1 weight ratio; fishmeal (B); bonemeal (C); bunch ash (D) and combinations EFB+POME, FM, BM and BA in different proportion to achieve the initial C:N ratio of 35 (Compost E), 42 (Compost F) and 47 (Compost G) were prepared. Sawdust was added into Compost E, F, G as Carbon regulator. The results indicated that the compost maturation was achieved on day 40 based on stable temperature and pH profiles. The changes in initial to final C:N ratio were at 59.8 to 29 (A), 3.69 to 7.4 (B), 8.13 to 10.8 (C), 42.3 to 23 (D), 35 to 16 (Compost E), 42 to 15 (Compost F) and 47 to 22 (Compost G). Fishmeal and bonemeal could enhance the nitrogen (N) and potassium (P) of compost but it was found that composting them alone resulted in pest problem due to the pungent rotten smell. Compost G with initial C:N of 47 produced final compost of C:N 22, suggesting for suitable organic formulations for a healthy compost C:N value and possibly with enhanced quality as compared to EFB compost alone. Future work will focus on establishing the quality of compost in terms of NPK and other elemental compositions. Â© Published under licence by IOP Publishing Ltd.